Human renal tubular epithelial cells suppress alloreactive T cell proliferation. (March 2015) - Demmers, M. W. H. J.; Korevaar, S. S.; Roemeling‐van Rhijn, M.; van den Bosch, T. P. P.; Hoogduijn, M. J.; Betjes, M. G. H.; Weimar, W.; Baan, C. C.; Rowshani, A. T.
Summary Renal tubular epithelial cells (TECs) are one of the main targets of alloreactive T cells during acute rejection. We hypothesize that TECs modulate the outcome of alloimmunity by executing immunosuppressive effects in order to dampen the local inflammation. We studied whether TECs possess immunosuppressive capacities and if indoleamine 2, 3‐dioxygenase (IDO) might play a role in suppressing T cell alloreactivity. Next, we studied the role of programmed death ligand 1 (PD‐L1) and intercellular adhesion molecule‐1 (ICAM‐1 with regard to TEC‐related immunomodulatory effects. CD3/CD28 and alloactivated peripheral blood mononuclear cells were co‐cultured with activated TECs. We analysed CD4+ and CD8+ T cell proliferation and apoptosis in the absence or presence of IDO inhibitor 1‐methyl‐L‐tryptophan (1‐L‐MT), anti‐PD‐L1 and anti‐ICAM‐1. Further, we examined whether inhibition of T cell proliferation was cell–cell contact‐dependent. We found that TECs dose‐dependently inhibited CD4+ and CD8+ T cell proliferation (P < 0·05). Activated TECs showed significantly increased IDO activity and up‐regulated PD‐L1 and ICAM‐1 expression. Suppressed CD4+ and CD8+ T cell proliferation was only partially restored or failed to restore using 1‐L‐MT. Activated TECs increased early and late apoptosis of proliferating CD4+ and CD8+ T cells; only CD4+ T cell apoptosis was statistically affected by 1‐L‐MT. Transwell experiments revealed that TEC‐mediated immunosuppression is cell–cell contact‐dependent. We found that anti‐ICAM‐1 affected only CD4+ T cell apoptosis and not T cell proliferation. Our data show that TECs suppress both CD4+ and CD8+ T cell proliferation contact dependently. Interestingly, inhibition of proliferation and enhancement of apoptosis of T cell subsets is differentially regulated by indoleamine 2, 3‐dioxygenase and ICAM‐1, with no evidence for the involvement of PD‐L1 in our system.